Suitability of Multinutrient Extractants for Evaluation Of Available Soil Zinc for Tomato Nutrition Of Karnataka Soils - Prasad, PN Siva; Subbarayappa, CT (Bangladesh Journal of Botany, 2022)
Pot experiment was conducted at University of Agricultural Sciences, Bangalore, Karnataka, which received five treatments i.e., 0, 5, 10, 15, 20 kg ZnSO4/ha. Among all the treatments Recommended NPK + ZnSO4 @ 20 kg/ha recorded highest mean dry matter yields of tomato. The amount of zinc extracted by different extractants were in the following order as Mehlich-3 - Zn > 0.1 N HCl - Zn > AB-DTPA - Zn > 0.01 N EDTA - Zn > DTPA - Zn > 0.01 M EDTA + 1 N NH4OAc - Zn > 1 N NH4OAc (pH 4.6) - Zn > 1 N NH4OAc (pH 7) - Zn. Among the various extractants tried DTPA - Zn gave positive and higher significant correlation with Brays per cent Yield (r = 0.781). The next better extractants were Mehlich-3 (r = 0.726) and AB-DTPA (r = 0.576) which were also significantly positively correlated with Brays per cent yield. The critical limits of DTPA, Mehlich-3, AB-DTPA, tomato plant and tomato fruit by graphical method were 1.12, 2.15, 1.20, 34 and 58 mg/kg, respectively. Bangladesh J. Bot. 51(4): 655-662, 2022 (December)